Prevention of Adolescent Anemia Through Posyandu and Education - Ardiansyah, Irman Syahrul (Jurnal Pendidikan Kesehatan, 2024)
Anemia are a major public health problem, especially affecting children, pregnant and postpartum women, as well as adolescent girls and women who are menstruating. Anemia in adolescent girls is still quite high. This article aims to look at preventing anemia in adolescents. This research uses a literature review method by analyzing articles obtained from databases according to the research topic. The results of the article selection resulted in 10 articles that were feasible and met the criteria. Prevention of anemia in adolescents can be done through youth posyandu activities and cadre formation and providing education. Providing education related to preventing anemia in teenagers can be done through focus group discussions (FGD), counseling, e-booklets, and youth empowerment. There needs to be support from various parties so that prevention of adolescent anemia is more optimal.